The 21st annual International Symposium on Computer Architecture April 18-21, 1994, Chicago, Illinois : proceedings (IEEE Computer society Press, 1994)
Proceedings of the April 1994 symposium, containing 34 papers covering subjects such as branch prediction, two-level cache design, performance evaluation, multiprocessor design, vectors, speculative memory access, disk I/O architecture, benchmarks, shared memory multiprocessor design, and design trade-offs.